PENERAPAN PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA KELAS XI IPA.2 SMAN 6 PEKANBARU - Lasma Br Hotang (Jurnal Pendidikan, 2018)
This research aimed to improve the ability of the phisic subject XI IPA2 SMAN 6 Pekanbaru students. Students were not encouraged to develop critical thinking skills where the results obtained are only 8 out of 32 (24%) students who complete while the other 25 (76%) students have not yet reached KKM (Minimum Completeness Criteria). The research method used was the Classrom Action Research (CAR) which consist of 2 cycles. Before the treatment was performed, the students were given a pre-test, and after the treatment a post-test was administered. The research findings The average daily test scores were 68.33 enough categories and in the second cycle the number of students whose grades were complete were 30 people (91%) with "Good" criteria and the number of unfinished students was 3 (9%). The average daily test for all completed students was 83.33 with the highest score of 95, and the average daily test for the unfinished 63.33 with the lowest score of 55. The overall daily test score was 81.51 in the good category. Then it can be concluded that the application of problem solving learning models can improve learning outcomes of physics for students in class XI IPA 2 of SMAN 6 Pekanbaru.